COVID-19 highlights the need for universal adoption of standards of medical care for physicians in nursing homes in Europe - O'Neill, Desmond; Briggs, Robert; Holmerová, Iva; Samuelsson, Olafur; Gordon, Adam L; Martin, Finbarr C; Special Interest Group in Long Term Care of the European Geriatric Medicine Society (European geriatric medicine, 2020)
The nursing home sector has seen a disproportionately high number of deaths as part of the COVID-19 pandemic. This reflects, in part, the frailty and vulnerability of older people living in care homes but has also, in part, been a consequence of the failure to include care homes in the systematic planning of a response to COVID, as well as a measure of neglect of standards and quality improvement in the sector. In response, the EUGMS published a set of medical standards of care developed in consultation with experts across its member national societies in 2015. The standards consisted of seven core principles of medical care for physicians working in nursing homes as a first step in developing a programme of clinical, academic and policy engagement in improving medical care for older people who are living and frequently also dying as residents in nursing homes. The gravity of the concerns arising for nursing home care from the COVID-19 pandemic, as well as emerging insights on care improvement in nursing homes indicate that an update of these medical standards is timely. This was performed by the writing group from the original 2015 guidelines and is intended as an interim measure pending a more formal review incorporating a systematic review of emerging literature and a Delphi process.
Keywords: pandemie; COVID-19; poskytování zdravotní péče; senioři nad 80 let; domovy pro seniory; delfská metoda; Humans; geriatrické hodnocení; Delphi Technique; MeSH; Aged, 80 and over; Europe; Health Services Needs and Demand; lékařská praxe - způsoby provádění; Delivery of Health Care; Homes for the Aged; virová pneumonie; mužské pohlaví; příčina smrti; Nursing Homes; Standard of care; pečovatelské domovy; Patient Care Team; Evropa; koronavirové infekce; Coronavirus Infections; Geriatric Assessment; ženské pohlaví; zdravotnické služby - potřeby a požadavky; Physicians; lékaři; týmová péče o pacienty; lidé; Nursing home; Pandemics; Pneumonia, Viral; analýza přežití; Practice Patterns, Physicians'; Aged; senioři; Male; Cause of Death; Survival Analysis; Female